THE USE OF ADDRESS FORM IN HITCH MOVIE: A SOCIOLINGUISTIC STUDY - Abdul Khalik (Vivid: Journal of Language and Literature, 2012)
This article discusses the address forms used in a conversation. The study is aimed at explaining the background of the use of address forms and social dimension which is reflected from the use of the address forms in the interaction. The data are taken from a movie entitled "Hitch", produced in 2005. Data were collected through observational method and supported by recording techniques to identify the use of address forms in the movie. At the same time, to support data analysis, the writer also takes pictures of the characters when using the address forms in the movie. Data were analyzed by using the pragmatic identity method referring to Wardaugh’s theory and supported by Holmes’ theory about the social dimension. After analyzing 14 data, it is found that there are 3 (21.4%) use of the address form of titles, 3 (21.4%) use of the first name, one (7.2%) use of the last name, 5 (35.7%) use of nickname, and 2 (14.3%) use of title and last name. While the factors behind the use of address forms are: to show politeness, seriousness of the subject, respect, familiarity with the speaker, compassion, and to greet the other person. The use of address forms illustrates the scale of social relations, the status scale, formality scale, and affective and function of scale.